Pengendalian Internal Sebagai Pemoderasi Pengaruh Kompetensi Sumber Daya Manusia Terhadap Kualitas Laporan Keuangan Daerah - Paulina Rosna Dewi Redjo (Ekopem: Jurnal Ekonomi Pembangunan, 2020)
ABSTRACT This type of research is quantitative by using a survey method that was conducted in North Central Timor District. The sample in this study used all existing DPOs to represent past and future DPOs. The variables used are human resource competence (X), government internal control (M) and the quality of financial reports (Y). The data analysis used the Structural Equation Modeling (SEM) method to test the two hypotheses proposed in this study. Each hypothesis will be analyzed using Partial Least Square (PLS) software, namely the WarpPLS version 3.0 software. to test the relationship between variables. The results of the analysis show that there is an influence between human resource competence on the quality of financial reports in the district government of North Central Timor. The test results with the moderating variable show that there is no influence of HR competence on the quality of financial reports in the TTU district government which is moderated by the government's internal control system.